From Reparations to Respectability: The Tinne Family of Liverpool. Issue 2 (1st December 2022) - Cardona, Mylynka Kilgore
Abstract : This article investigates generational wealth and the legacy of slave ownership in the Atlantic World, and specifically, how over time, generations filter out their connections to transatlantic slavery (and the trade of enslaved-produced goods) as the source of their family wealth and status. This article looks at how class status changes and how the taint of slave ownership fades away in the latter nineteenth century to be replaced in the twentieth and twenty-first centuries by labels like 'sugar merchant' with no mention of who produced said commodity-based wealth, using as a case study the Tinne family of Liverpool. This article touches on aspects of imperialism and empire, transatlantic and transnational history, public history, historical memory, the transatlantic slave trade, and the impact of the Slave Emancipation Act on global labour migrations.